Corporate governance, gender diversity and firm’s value of listed banking companies - Jubilee, Ribed Vianneca W. (2018)
Corporate Governance and Gender Diversity in boardroom has been associated with firm value and it’s had become one of the focuses of related study. This study examines the relation of corporate governance and gender diversity on the board of directors to firm value (Tobin’s Q) for the data set of 10 listed commercial banks in Bursa Malaysia on year 2007 to 2016. In this study, we employ panel data analysis for regression test. This study investigates the relationship between corporate governance and women on board of director with the firm value. In general, this study contributes to the literature by examine the issue of gender diversity in corporate boards and aims to provide empirical evidence relation to regulatory and banking sector environment in Malaysia. This study found a positive relationship between proportion of female director to the firm value (Tobin’s Q). Moreover, the results also indicate that independent female director on the corporate board has a negative relationship to firm value (Tobin’s Q). This study sheds new light on the effect of gender diversity in Malaysian banking sector boardroom as the government make efforts pursues policies to increase the participation of women in the top management.